(untitled) (Plant Tissue Culture and Biotechnology, 2013)
Genetic diversity of 11 tomato (Lycopersicon esculentum Mill.) varieties was assessed through RAPD analysis. Twenty arbitrary oligonucleotide primers used in the RAPD?PCR produced a total of 584 different marker bands with an average of 29.2 bands per primer. Based on the banding pattern 94.168% polymorphism observed among the tomato varieties. Size range of amplified DNA bands varied from 0.1 ? 10 kb. A total of 15 unique bands were amplified from the genome of the 11 tomato varieties. The values of pair?wise genetic distances ranged from 0.1838 - 0.9049, indicating the presence of wide genetic diversity. The dendogram constructed based on phylogenetic relationship analysis revealed that the highest genetic diversity (0.9049) found between the variety BARI Tomato 8 and RATAN whereas the lowest (0.1838) between the variety BARI Tomato 9 and MADHURI. The dendogram has segregated the 11 tomato varieties into two major clusters. RATAN and SPECIAL?OP formed cluster 1 and rest 9 varieties viz., ROMA?VF, MARGLOBE, MADHURY and BARI Tomato 9, 2, 6, 14, 8 and 3 have constituted the second cluster. Plant Tissue Cult. & Biotech. 23(1): 49?57, 2013 (June) DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15559